A Review of Safety, Quality, Regulation, and Delivery Approaches for Phytopharmaceuticals - K, Pavithra; V, Manimaran (Jordan Journal of Pharmaceutical Sciences, 2024)
Phytopharmaceuticals are plant-derived compounds with a wide range of potential health benefits. Their unique characteristics and versatile applications make them promising candidates for the treatment of many diseases. Phytopharmaceuticals contain a wide range of bioactive components, including alkaloids, terpenes, and flavonoids. These compounds have a variety of biological activities, including antioxidant, anti-inflammatory, and antimicrobial effects. In recent years, there has been growing interest in phytopharmaceuticals for the treatment of various conditions, including cancer, cardiovascular disease, and diabetes. However, more research is needed to fully understand the efficacy and safety of these compounds. To ensure the quality and safety of phytopharmaceuticals, quality management procedures have been developed based on the principles of the World Health Organization (WHO) and Good Agricultural and Collection Practices (GACP). Understanding these regulations is essential for assuring effective phytopharmaceutical product development, manufacture, and distribution. While phytopharmaceuticals have shown promise in laboratory research, there are challenges in translating their efficacy to effective clinical applications, particularly in terms of delivery. Innovative approaches, such as targeted delivery methods and nanoparticle-based strategies, are needed to overcome these challenges. This review provides a comprehensive overview of the challenges and opportunities in the field of phytopharmaceuticals.